A CONCEPTUAL STUDY ON THE FACTORS INFLUENCING USAGE INTENTION OF E-WALLETS IN JAVA, INDONESIA - Chyntia Angelina; Raden Aswin Rahadi (International Journal of Accounting, Finance and Business, 2020)
Indonesia is leading towards digital economy and electronic payment system. One of the most popular and widely used electronic payment system in Indonesia is electronic wallet, or usually called e-wallet. This study aims to provide a proposed model to determine the factors influencing e-wallet usage intention in Java, Indonesia. In this study, the researcher proposed a modified framework from author analysis based on 18 previous literature studies, which consists of 6 independent variables such as: performance expectancy; effort expectancy; social influence; perceived security; hedonic motivation; and relative advantage; which lead to a dependent variable, namely usage intention. The hypotheses on the proposed framework of this study will be tested, taking the sample of Generation Z, to determine the factors that extend the use of e-wallet in Java, Indonesia. The discoveries will be useful as reference for further studies on analysing nor evaluating the use of e-wallet payment, to support the rapidly growing cashless society in Indonesia.